SUSTAINABLE SUPPLY CHAIN MANAGEMENT STRATEGY: TOWARDS EFFICIENCY, INNOVATION, AND ENVIRONMENTAL RESPONSIBILITY - Imam Wibowo (BIOS: Jurnal Informatika dan Sains, 2023)
Sustainable supply chains are becoming increasingly important in this era of globalization, where companies are required to not only achieve economic profits, but also pay attention to the social and environmental impacts of their operational activities. This research aims to analyze and identify sustainable supply chain management strategies to achieve operational efficiency, product innovation and environmental responsibility. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of sustainable supply chain management strategies has a positive impact on company performance in efficiency, innovation and environmental responsibility. Identifying critical points in the supply chain, selecting suppliers committed to sustainable practices, and leveraging technology in production processes drives positive change. Transportation optimization, sustainability performance monitoring systems, and active engagement with stakeholders have also been proven to make a real contribution in establishing a more responsive and responsible supply chain. Through these steps, companies can achieve operational success while minimizing negative impacts on the environment, as social responsibilities are increasingly strengthened and recognized.